Burton field guide for industrial hygiene - Burton, D. J. (AIHA, 2021)
Raw technical data from an engineering perspective makes Jeff Burton's Field Guide a uniquely useful tool. Presented in a concise, handy format, this guide contains everything you need to know on common industrial gases and chemicals and provides checklists for exhaust fan maintenance, indoor air contaminant sources, and much more. Chapters include terms, equations, monographs, and charts and cover thermal conditions, ergonomics, PPE and respirators, standards and guidelines, and sound and noise.
Keywords: Industrial hygiene -- Handbooks, manuals, etc.; Environmental health -- Handbooks, manuals, etc.; elektronické knihy; electronic books